PERAMALAN PRODUKSI CABAI RAWIT PROVINSI JAWA BARAT MENGGUNAKAN METODE HOLT-WINTERS - Asri Yuniar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The spiciness of cayenne pepper, not only in the mouth, but also can affect thenational economy. Cayenne pepper (Capsicum frutescens) is one of the horticulturalplants of a type of vegetable that has small fruit with a spicy taste. The skyrocketingprice of cayenne pepper can be a driver of national inflation. The first step tosuppress the increase in the price of cayenne pepper is to have the required numberof cayenne pepper production, which can be modeled mathematically through aforecasting method which is one of the tools in making decisions based on past datasets. The appropriate method to be used in this research is the holt-winters methodbecause the fluctuating data contains seasonal patterns. The results of the studyshowed that the use of the Holt-Winters method with multiplicative seasonal typeobtained good forecasting results with a MAPE of 13.68 percent to predict theproduction of cayenne pepper in West Java Province.